Fluid Flow Analysis in Cisarua Hot Spring, South Lampung: A Study Using Geoelectric and Induced Polarization Methods - Fadhiah Nurul Aini; Joan Margareth Sihol Marito S; Selvi Misnia Irawati (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
Characterization of subsurface hydrothermal fluid flow pathways is essential for exploration and sustainable development of fault-controlled, non-volcanic geothermal systems. The Cisarua Hot Spring in Natar District, South Lampung, is a non-volcanic geothermal system controlled by the northwest-southeast trending Lampung–Panjang Fault; however, the hydraulic connectivity between the old well and new well manifestations has not been previously demonstrated geophysically. This study presents the first integrated Electrical Resistivity Tomography (ERT) and Induced Polarization (IP) investigation to map subsurface connectivity between both manifestation sources, aiming to identify hydrothermal fluid pathways and determine the hydraulic interconnection between the two wells. A Wenner–Schlumberger survey was conducted along four 235 m measurement lines with a maximum investigation depth of 44.65 m. Inversion results identify two principal lithologies: tuffaceous clay (resistivity <20 Ωm) and tuffaceous sand (20–33.6 Ωm). Zones of low resistivity coupled with elevated chargeability (>20 ms) on profiles 1 and 3 indicate active hydrothermal fluid pathways structurally controlled by the Lampung–Panjang Fault, with hydrothermally altered clay forming a confining layer above the reservoir. Results confirm that both wells constitute a single, internally connected hydrothermal system linked by a northwest-southeast trending fluid migration pathway along the fault zone.